Influence of Barn Yard Millet Flour on Quality Characteristics and Fatty Acid Profile of Chicken Meat Nuggets - Reddy M, Manikanta; Reddy G.V, Bhaskar; K, Sudheer; M, Varalakshmi; Renuka, U (Journal of Meat Science, 2026)
An investigation was conducted to evaluate the effect of incorporating barnyard millet (Echinochloa esculentum) flour (0, 2, 4, and 6 %) on the quality attributes and omega-3 fatty acid profile of chicken meat nuggets. Nuggets containing 6 % barnyard millet flour exhibited improved physicochemical properties, including higher cooking yield, emulsion stability, and water-holding capacity. Increasing levels of barnyard millet flour resulted in higher moisture, crude fiber, and ash contents, accompanied by a reduction in protein content. Textural quality was enhanced, as indicated by lower shear force values and improved textural attributes compared with the control. Instrumental colour scores increased with barnyard millet flour incorporation. Omega-3 fatty acid content was higher in nuggets formulated with 6 % barnyard millet flour. Sensory evaluation also indicated superior acceptability for nuggets containing 6 % barnyard millet flour. Overall, incorporation of barnyard millet flour at 6 % improved the quality characteristics and enhanced the omega-3 fatty acid content of chicken meat nuggets.